Management of miscarriage: expectant, medical, or surgical? Results of randomised controlled trial (miscarriage treatment (MIST) trial). Issue 7552 (17th May 2006) - Trinder, J; Brocklehurst, P; Porter, R; Read, M; Vyas, S; Smith, L
Abstract: Objective To ascertain whether a clinically important difference exists in the incidence of gynaecological infection between surgical management and expectant or medical management of miscarriage. Design Randomised controlled trial comparing medical and expectant management with surgical management of first trimester miscarriage. Setting Early pregnancy assessment units of seven hospitals in the United Kingdom. Participants Women of less than 13 weeks' gestation, with a diagnosis of early fetal demise or incomplete miscarriage. Interventions Expectant management (no specific intervention); medical management (vaginal dose of misoprostol preceded, for women with early fetal demise, by oral mifepristone 24-48 hours earlier); surgical management (surgical evacuation). Main outcome measures Confirmed gynaecological infection at 14 days and eight weeks; need for unplanned admission or surgical intervention. Results 1200 women were recruited: 399 to expectant management, 398 to medical management, and 403 to surgical management. No differences were found in the incidence of confirmed infection within 14 days between the expectant group (3%) and the surgical group (3%) (risk difference 0.2%, 95% confidence interval − 2.2% to 2.7%) or between the medical group (2%) and the surgical group (0.7%, − 1.6% to 3.1%). Compared with the surgical group, the number of unplanned hospital admissions was significantly higher in both the expectant group (risk difference − 41%, − 47% to − 36%) and the medical group (− 10%, − 15% to − 6%). Similarly, when compared with the surgical group, the number of women who had an unplanned surgical curettage was significantly higher in the expectant group (risk difference − 39%, − 44% to − 34%) and the medical group (− 30%, − 35% to − 25%). Conclusions The incidence of gynaecological infection after surgical, expectant, and medical management of first trimester miscarriage is low (2-3%), and no evidence exists of a difference by the method of management. However, significantly more unplanned admissions and unplanned surgical curettage occurred after expectant management and medical management than after surgical management. Trial registration National Research Register: N0467011677/N0467073587.